Managing conception and pregnancy for HIV serodiscordant couple : a case report - Sapiee S,; Leelavathi Muthupalaniappen, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Worldwide, there is an increasing number of people living with HIV and AIDS especially in the reproductive age group. This has a huge impact when they wish to start a family. Managing reproductive issues among serodiscordant HIV couples is complex and often presents as a challenge especially in minimizing the risk of transmission. We report a case of a HIV positive man and his seronegative wife who successfully achieve conception and deliver a healthy baby without disease transmission of HIV to mother or child. Both partners were managed with treatment where the HIV positive male partner was treated with HAART while the unaffected female partner was on PrEP and conception was achieved through intrauterine insemination (IUI). Planning of conception, the use of medications and options for conception methods will be discussed in detail.